OASI: an observatory dedicated to minor planets in the Solar System - Rodrigues, Teresinha (Cadernos de Astronomia, 2024)
This paper addresses the motivation, installation process, and operation of an astronomical observatory in Brazil dedicated to studying the physical processes of small bodies within the Solar System. From the proposal idealization in 2005 to the observatory's full functioning, several unsuspected challenges became part of the project's variables, extrapolating the technical-scientific limits. The results have also been exceeding expectations: in 13 years of operation, the Observatório Astronômico do Sertão de Itaparica (OASI) not only counts with good academic production but also maintains important collaborations with education and research institutions of the Brazilian Northeast region, seeking to include the society in the processes of thinking and doing science.
Keywords: Solar System; Observational Astronomy; National Observatory (Brazil)